Multiplication and division of fraction
Multiplication of Fractions
The product of the two fractions a/2 and c/d is defined in previous Chapter to be (ac)/(bd);
that is, a/b*c/d=(ac)/(bd)
Thus the product of two fractions is a fraction whose numerator is the product of the numerators and whose denominator is the product of the denominators. In general,
Note Always reduce the resulting fraction to lowest terms.
EXAMPLE Find the product of (27a^3b^2)/(8x^2y) and (16x^3y)/(81a^2b^3)
Note It is easier to reduce (27*16)/(8*81) then 432/648, which is the result of the products.
That is. numbers should not be multiplied together until the fraction has been simpliﬁed.
To multiply fractions whose numerators or denominators are polynomials, ﬁrst factor polynomials completely Consider the fractions as just one fraction, and divide the numerators and denominators by their greatest common factor to get an equivalent fraction in lowest terms.
EXAMPLE Simplify (x^2-3x)/(2x^2+11x+5)*(6x^2+x-1)/(3x^2-10x+3)
EXAMPLE Simplify (12x^2-13x+3)/(3x^2-5x-2)*(2x^2-x-6)/(9-6x-8x^2)
Division of Fractions
From the deﬁnition of division of fractions, discussed before, we have
a/b ÷ c/d = a/b*d/c
The above result shows how to transform division of fractions into multiplication of fractions.
The fractions c/d and d/c are called multiplicative inverses or reciprocals
Note The reciprocal of the expression a+b is 1/(a+b, not 1/a+1/b
Note The reciprocal of 1/a+1/b is 1/(1/a+1/b), or simplified, ab/(b+a)
EXAMPLE Simplify (3a^3)/(5b^2) ÷ (9a^2)/(20b)
Solution (3a^3)/(5b^2) ÷ (9a^2)/(20b)== ((3a^3)/(5b^2)) *((20b)/(9a^2))== (4a)/(3b)
Note Note The difference between
a/b÷ (c/d*e/f) == a/b*d/c*e/f == ade/bcf
a/b÷(c/d*e/f)== a/b ÷ ce/df== a/b*df/ce== adf/bce
EXAMPLE Simplify (9a^2b^4)/(49x^2y^3) ÷ (a^2b)/(14x^2y)*(21y)/(ab^2)
(9a^2b^4)/(49x^2y^3) ÷ (a^2b)/(14x^2y)*(21y)/(ab^2)==(9a^2b^4)/(49x^2y^3)*(14x^2y)/(a^2b)*(21y)/(ab^2)==(54b)/(ay)
EXAMPLE Simplify (a^3b^2)/(x^2y^3) ÷ ((a^2b^5)/(x^5y)*(x^3y^2)/(ab^3))
(a^3b^2)/(x^2y^3) ÷((a^2b^5)/(x^5y)*(x^3y^2)/(ab^3))==((a^3b^2)/(x^2y^3)) ÷ ((a^2b^5*x^3y^2)/(x^5y*ab^3))==(a^3b^2)/(x^2y^3)*(x^5y*ab^3)/(a^2b^5*x^3y^2)==a^2/y^4
EXAMPLE Simplify (8x^2+2x-3)/(4x^2-17x-15) ÷ (12x^2-20x+7)/(6x^2-37x+35)
Solution As in multiplication of fractions, we factor the numerators and denominators
|← Previous Tutorial||Next Tutorial →|